Cognitive psychology - Goldstein, E. Bruce (Hampshire, United Kingdom Cengage Learning EMEA, 2024)
"Connecting the study of cognition to everyday life, Goldstein and van Hooff's bestselling text Cognitive Psychology provides an accessible and engaging introduction to the subject, giving insight into the many psychological and physiological aspects of human behaviour. Now in its third edition and containing the latest stimulating research, this text helps students navigate through all the major sub-disciplines and key concepts of cognitive psychology. It facilitates development of a thorough understanding of the complex relationships between mind, brain and behaviour. Through the authors' international approach and emphasis on research, methodology and application, students learn how to interpret theories and then use them in practical applications."-- Provided by publisher.
Keywords: Cognitive psychology